Odpowiedzi

2010-03-23T19:29:02+01:00
A)7x-3(5x+2)-6(7+2x)=7x-15x-6-42-12x=-20x-48
b)-5(3y-7)-2(6+4y)+3y=-15y+35-12-8y+3y=-20y +23
c)4c-(3c+2)-10c=4c-3c-2=c-2
d)7x-8-(5x+6)=7x-8-5x+6=2x-2
e)9y+(8-3y)+16=9y+8-3y+16=6y+24
f)-2a(4a-1)+5a(3a+2)=-8a(kw)+2a+15a kw+10a=7a kw+12a
g)3a(b-5a)-2a(3b+a)=3ab-15a kw-6ab-2a kw=17a kw -3ab
h)-5x(2x+3y)+x(x-2y)= -10x kw -15xy+xkw-2xy=-x kw-17xy-10x
2010-03-23T19:33:02+01:00
A)7x-3(5x+2)-6(7+2x)= 7x-15x-6-42-12x=-20x-48

b)-5(3y-7)-2(6+4y)+3y=-15y+35-12-8y+3y=-20y+23

c)4c-(3c+2)-10c=4c-3c-2-10c= -9c-2

d)7x-8-(5x+6)=7x-8-5x-6= 2x-14

e)9y+(8-3y)+16=9y+8-3y+16=6y+24

f)-2a(4a-1)+5a(3a+2)=-6a kwadrat+2a -15a kwadrat +10a= -9akwadrat +12a


g)3a(b-5a)-2a(3b+a)=3ab-15akwadrat -2ab-2a kwadrat= ab - 17a kwadrat'


h)-5x(2x+3y)+x(x-2y)= -10xkwadrat -15xy+xkwadrat -2xy=-9xkwadrat-17xy